1992
DOI: 10.1164/ajrccm/146.1.132
|View full text |Cite
|
Sign up to set email alerts
|

Role of Potassium Channels in Bronchodilator Responses in Human Airways

Abstract: The plasma membrane of airway smooth muscle contains a high density of K+ channels of various types that mainly regulate membrane potential. To examine whether these K+ channels are involved in bronchodilating mechanisms in human airways, relaxation concentration-response studies to isoproterenol, theophylline, and a K(+)-channel opener, lemakalim (BRL 38227), were obtained in the presence or absence of charybdotoxin (ChTX) (10 or 100 nM), an inhibitor of large conductance Ca(2+)-activated K+ channels (KCa) in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
74
2

Year Published

1993
1993
2006
2006

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 133 publications
(82 citation statements)
references
References 8 publications
6
74
2
Order By: Relevance
“…These channels, which are composed of four subunits, are abundant in ASM and are a substrate for PKA [89,[91][92][93]. Furthermore, their role in regulating ASM contractility is suggested from the finding that pharmacological blockade of these channels with charybdotoxin, and the more selective iberiotoxin, prevents hyperpolarisation and b 2 -adrenoceptor-mediated relaxation [93][94][95][96]. …”
Section: Adrenoceptors In the Lungmentioning
confidence: 99%
“…These channels, which are composed of four subunits, are abundant in ASM and are a substrate for PKA [89,[91][92][93]. Furthermore, their role in regulating ASM contractility is suggested from the finding that pharmacological blockade of these channels with charybdotoxin, and the more selective iberiotoxin, prevents hyperpolarisation and b 2 -adrenoceptor-mediated relaxation [93][94][95][96]. …”
Section: Adrenoceptors In the Lungmentioning
confidence: 99%
“…We have not addressed the airway selectivity of this drug in the present study, but HOE 234 was found to have more potent dilatory effects, in human bronchi, than was previously reported for ATP-sensitive K+ channel opener BRL 38227 (Miura et al, 1992). If HOE 234 is to be potentially useful in the treatment of bronchial asthma further experiments must be carried out to ascertain the airway selectivity of this drug compared to its effects on vascular smooth muscle.…”
Section: Discussionmentioning
confidence: 78%
“…Bronchodilating effects of a K+ channel opener, BRL 38227, have been reported by Black and co-workers (1990) on human airway smooth muscle. We have previously shown that BRL 38227 relaxes human bronchi effectively and that this relaxation is inhibited by ATP-sensitive K+ blocker, BRL 31660, but not by charybdotoxin or apamin which block large or small conductance Ca2+-activated K+ channels, respectively (Miura et al, 1992). HOE 234 was significantly more potent at producing relaxation than BRL 38227 in comparable tissues on both spontaneous and increased tone, although the maximum relaxation produced by the two drugs was similar.…”
Section: Discussionmentioning
confidence: 87%
“…These are summarized in table 2. Because membrane hyperpolarization causes myocyte relaxation, stimulation of the calcium-activated potassium channel (K Ca , also called BK or Maxi K) results in relaxation [33]. The mechanisms underlying regulation of K Ca have been dissected over the last few years and it is now clear that this channel is subject to complex regulation, being stimulated by both Gsa directly [34] and the catalytic subunit of protein kinase A [35].…”
Section: Relaxation Through Gs-coupled Receptorsmentioning
confidence: 99%